Auxetic polyurethane stents and stent-grafts for the palliative treatment of squamous cell carcinomas of the proximal and mid oesophagus: A novel fabrication route. (October 2015) - Ali, Murtaza Najabat; Rehman, Ihtesham Ur
Highlights: Development of novel and cost-effective Auxetic oesophageal stent. Significantly small diameter Auxetic stent to facilitate oral insertion. Both conventional subtractive and new additive manufacturing approach was adopted. Lasercutting is effective, rapid and less expensive fabrication method. Lasercut Auxetic stent expands in both radial and longitudinal directions. Abstract: Squamous cell carcinoma is usually cancer of the upper oesophagus and is very aggressive cancer. The cancer of the cervical oesophagus causes a serious complication called dysphagia, which is difficulty in eating or swallowing and which is indicative of incurability. Oesophageal stents have been used as a relatively better palliative method for patients who are suffering from advanced stage squamous cell carcinomas of oesophagus and also for the effective relief of dysphagia. There are still problems in currently available self-expanding metals and plastic stents, which are associated with high rates of early and late complications. This research work is aimed to use Auxetic (rotating-squares) geometry for the production of a novel Auxetic oesophageal stents and stent-grafts relevant to the palliative treatment of squamous cell carcinomas of the proximal and mid oesophagus and also for the prevention of dysphagia. This study also endeavoured to manufacture a significantly small diameter Auxetic oesophageal stent and stent-graft. In order to easily deploy the Auxetic stent orally using a commercial balloon dilatational catheter, and hence it also obviates the need of an expensive dedicated delivery system. A novel manufacturing route was employed in this research to develop both Auxetic films and Auxetic oesophageal stents, which ranged from conventional subtractive techniques to new generative manufacturing methods. Polyurethane was selected as a material for the fabrication of Auxetic films and Auxetic oesophageal stents because of its good biocompatibility and non-toxicological properties. The developed Auxetic films were later used for the fabrication of seamed Auxetic oesophageal stents. The flexible polyurethane tubular grafts were also attached to the inner luminal side of the seamless Auxetic oesophageal stents, in order to prevent tumour in-growth.